Cellular and humoral immunity to hepatitis-B surface antigen in active chronic hepatitis. Issue 5960 (29th March 1975) - Lee, W M; Reed, W D; Mitchell, C G; Galbraith, R M; Eddleston, A L; Zuckerman, A J; Williams, R
Abstract : The hepatitis-B surface antigen (HBsAG) may be persistently present in the serum in a few cases of active chronic hepatitis but the cause of the disease in most patients is unknown. In a study of 39 HBsAg-negative cases cell-mediated immunity to HBsAg was observed in 24 (62%), suggesting a high frequency of previous infection with the hepatitis-B virus. Hepatitis-B surface antibody was detectable by radioimmunoassay in six patients, in all of whom complexes of HBsAg were present in the serum on electron microscopy. Out of 12 patients with HBsAg-positive active chronic hepatitis who were also studied eight, including all those untreated at the time, showed a cellular response to the antigen. Evidence of sensitization to a liver-specific cell surface lipoprotein was found with similar frequency in the two groups. These results are consistent with the hypothesis that hepatitis-B virus infection is important in initiating the disease in many cases of active chronic hepatitis and that sensitization to the liver cell membrane antigen is the autoimmune process responsible for the perpetuation of the liver injury.